The complete chloroplast genome of Saussurea medusa maxim. (Asteraceae), an alpine Tibetan herb. Issue 11 (2nd November 2021) - Wei, Yongsheng; Zhang, Zhiwei; Wang, Changhua; Su, Yan; Ye, Chenjuan; Pan, Rui; Liu, Xiang; Qu, Xianyou; Lan, Xiaozhong
Abstract: Saussurea medusa is an important traditional Tibetan medicinal plant in China. In this study, we assembled the complete chloroplast (cp) genome of S. medusa . The complete S. medusa chloroplast genome is a circular molecular structure of 152, 257 bp in length with coding GC 37.93%, consisting of two inverted repeats (25, 204 bp) separated by a large single-copy region (83, 334 bp) and a small single-copy region (18, 515 bp). The complete chloroplast genome of S. medusa contained 130 genes, including 87 protein-coding genes, 35 tRNA genes, and eight rRNA genes. Phylogenetic analysis shows that S. medusa is most closely related to Saussurea inversa and Saussurea pseudoleucoma . The complete chloroplast genome sequence of S. medusa facilitates the phylogenetic studies of Asteraceae.